2008
DOI: 10.1007/s10620-008-0566-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Treatment of Octreotide on Chylous Ascites After Liver Cirrhosis

Abstract: Octreotide is a crucial drug used for treating patients with chylous ascites; however, there have been few reports related to octreotide that are being used in cirrhotic patients. Thus, this thesis is designed to determine the effects of octreotide on patients with chylous ascites after liver cirrhosis. Eight patients were diagnosed with chylous ascites, on the basis of laboratory findings on ascites samples, between January 2003 and May 2008. Octreotide was given to the six patients, while the remaining two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…Although the late onset and prolonged evolution of this ascites were not in favour of this diagnosis, some authors have demonstrated that increased portal pressure, in the cirrhotic liver for example, is a risk factor for chylous ascites [12,13], and the initial clinical course with a diuretic and suitable diet was satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the late onset and prolonged evolution of this ascites were not in favour of this diagnosis, some authors have demonstrated that increased portal pressure, in the cirrhotic liver for example, is a risk factor for chylous ascites [12,13], and the initial clinical course with a diuretic and suitable diet was satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…And many herbal medicines are now being collected and examined in an attempt to identify possible sources of anti-liver injury. Natural compounds, because of their structural diversity, provide a good opportunity for screening for anti-liver injury agents 21) . In general, pharmacopuncture treatment is performed by injecting small amounts of extracted medicinal materials at acupuncture points or in affected areas in order to obtain combined efficacies of the acupuncture and herb.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Octreotide was first reported to significantly reduce chylous effusion in an adult with chylothorax 13 and subsequently in several other patients with various etiology. [14][15][16][17][18] Octreotide is a somatostatin analogue that inhibits the secretion of some pituitary and gastrointestinal hormones, reduce secretion of fluids from the intestine and pancreas, causes vasoconstriction in the blood vessels& increases splanchnic arteriolar resistance, reducing gastrointestinal flow and consequently the lymph flow. 17 It is a pharmacologic agent that also augments the closure of any leakage in the lymphatic system.…”
Section: Fig-1: Doses Of Octreotidementioning
confidence: 99%
“…In addition, variationsregarding octreotide dosing regimens (0.5-8 mcg/kg/h), modes of drug administration (intravenous or subcutaneous), commencement and duration of treatment have beenreported in the literature. 15,16 We used octreotide by intravenous infusion at a rate of 0.5ìg/kg/h and gradually increased to 1 ìg/kg/h on day 3 and continued till day 7 then tapered and discontinued on day 10.Huanget al 8 also used same dose and duration. A dramatic decrease in chyleproduction was observed within 24 hours of infusion, with complete resolution of ascites by 10…”
Section: Fig-1: Doses Of Octreotidementioning
confidence: 99%